2019
DOI: 10.3390/buildings9110229
|View full text |Cite
|
Sign up to set email alerts
|

Durability of Stone Cladding in Buildings: A Case Study of Marble Slabs Affected by Bowing

Abstract: Bowing is an uncommon pathology that can affect marble stone cladding of building façades, causing a large permanent deflection and the degradation of the flexural and anchoring strength of the stone slabs, which can lead to the cladding falling from the façades. Moreover, the combination of bowing with wind pressure effects on the building façades can increase the risk of fracture and collapse of the stone slabs, especially if this combination is not properly evaluated during design. Motivated by a case study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…In addition, the method and way of installing the finished stone products are of significant importance. This is confirmed by the many drawbacks and problems associated with the use of these natural building materials [16,[30][31][32][33][34][35].…”
Section: Scientific Backgroundmentioning
confidence: 81%
See 1 more Smart Citation
“…In addition, the method and way of installing the finished stone products are of significant importance. This is confirmed by the many drawbacks and problems associated with the use of these natural building materials [16,[30][31][32][33][34][35].…”
Section: Scientific Backgroundmentioning
confidence: 81%
“…Considering the physical and mechanical properties of ornamental stones, it is possible to see their strong interdependence [37,[41][42][43][44][45][46][47]. Physical properties coupled with the mechanical behaviour of rocks are influenced by the mineralogical composition, degree of cementation, and grain size [7,31,[48][49][50][51][52][53]. More profoundly, Aladejare and Wang [37] showed that bulk density, specific gravity, and unit weight generally show low variability, while porosity and water content show high variability in igneous, sedimentary, and metamorphic rocks.…”
Section: Scientific Backgroundmentioning
confidence: 99%
“…Secondly, they leave the space for the more frequent renovations since their life-span reaches only 25 years (according to the warranties granted at the purchase), and, as it would be proved later in this research, the total pay-back of the investment capital is perfectly possible within this period. Frontini et al (2015), Sousa and Sousa (2019), Grelk et al (2007) In the following part of the research, the actual economic benefit of BIPV façade was calculated. The results are to be found in table 3 below.…”
Section: Resultsmentioning
confidence: 99%
“…These materials are less porous than porous sedimentary stones, which makes them more resistant to a marine environment [4,[42][43][44]. Nevertheless, large-size marble panels (height larger than 1.0 m) in a marine environment, in high temperatures, and in the presence of a moisture gradient suffer from the bowing failure mechanism; therefore, they are not recommended, especially under the influence of a marine environment [45][46][47][48]. The main cause of the deterioration mechanism in wetfixed stone cladding is the effect of cement mortar on the cladding stone.…”
Section: Discussionmentioning
confidence: 99%